Marco Polo was in China : new evidence from currencies, salts and revenues - Vogel, Hans Ulrich (Monies, markets, and finance in East Asia, 1600-1900, 2210-2876 ;, 2013)
Hans Ulrich Vogel offers an innovative look at the highly complex topics of currencies, salt production and taxes, commercial levies and other kinds of revenue as well as the administrative geography of the Mongol Yuan empire. The author's rigorous analysis of Chinese sources and all the important Marco Polo manuscripts as well as his thorough scrutiny of Japanese, Chinese and Western scholarship show that the fascinating information contained in Le devisament dou monde agrees almost pefectly with that we find in Chinese sources, the latter only available long after Marco Polo's stay in China. Hence, the author concludes that, despite the doubts that have been raised, the Venetian was indeed in Khubilai Khan's realm. -- Publisher.